Fostering Quality Entrepreneurship Education for Sustainable Development in Nigeria - Bukki, Abolaji O.; Bello, Ganiyu (NIU Journal of Social Sciences, 2017)
It is now widely accepted that entrepreneurship education has an important role in national development. This paper focuses on the importance of entrepreneurship education towards enhancing sustainable development in Nigeria. The strategies that can enhance sustainable entreprenurship education are also discussed. Lastly, The paper recommended that educational programmes at all levels of education should be designed tto provide the needed entrepreneurial skills for Nigerian Youth. Keywords: Entrepreneurship, Education, Sustainable, Development, and Quality